P576 Kerion: a nasty scalp infection. (June 2019) - Callanan, Ronan; Wong, Foong Ying; Tierney, Emma; Ramsay, Bart; Murphy, Anne-Marie
Abstract : Background/Aims: Kerion is a scalp condition that occurs in severe cases of scalp ringworm (tinea capitis) with the highest prevalence in children 3 to 10 years of age. It appears as an inflamed, thickened, pus-filled area, with scaly spots or patches of broken hair on the scalp. A kerion is treated with oral antifungal medicines because the fungus grows deep into the hair follicle where topical creams and lotions cannot penetrate. Oral corticosteroids are also started in cases where lesions are tender and to reduce the inflammation. Kerion is usually associated with infection by zoophilic dermatophytes, Tricophyton Verrucusom and Tricophyton Mentagrophyte, although other sources have been described. Our aim is to report an unusual scalp infection. Methods: The patient history, clinical presentation with photographs, examination and laboratory findings (skin scrapings were taken for mycology), treatment and outcome are described. Results: A previously well 6-year-old boy, of African origin, presented to the Paediatric Emergency Department with a 6-month history of scalp infection. It initially started on the right temporal region and was treated with Canesten cream for 6 months. There was no improvement and the condition was treated with Flucloxacillin a week prior to presentation to us, at which point it had worsened and started spreading to the rest of his scalp. On examination there was a raised demarcated lesion on his right temporal area which appeared crusted and discharge was noted. There were also multiple round, dry, scaly patches on his scalp which were not infected. The dermatology team commenced him on oral Itraconazole, Nizoral Shampoo and Paraffin Gel for 6 weeks, and oral steroids for 1 week. Conclusion: Kerion is not often seen in our paediatric department. This case raises awareness of a rarely seen condition in an Irish context.